EFEKTIVITAS PELAKSANAAN TUGAS PIMPINAN TERHADAP SISTEM PELAYANAN PUBLIK DI PERPUSTAKAAN KABUPATEN HALMAHERA SELATAN - Batlawi, Rusdi; Senduk, Jhony (ACTA DIURNA KOMUNIKASI, 2015)
Every organization must have a leader, without leader will be chaotic because there must be person who govern and lead effectively in achieving ts objectives. Supervisory leadership plays an important role in improving employsee staff as one of the main reasons a person works is to mee ends of benefits they receive from working. The method used in this research is Qualitative research that describes the facts or events that occur in the field. The conclusion of this research : system monitoring employee performance leader in Southern Halmahera district library is not maximized. Factors that cause less maximum system control functions leader is less that the maximum, background experience in the field of library employees are still minimal.